Pornographic sensibilities
1 online resource
Keywords: Pornographic Sensibilities stages a conversation between two fields--Medieval/Early Modern Hispanic Studies and Porn Studies--that traditionally have had little to say to each other. The collection offers innovative new approaches to the study of gendered and sexualized bodies in medieval and early modern textual production, including literary and historical documents. The volume's embrace of the interpretative tools of Porn Studies also inscribes a critical provocation: in what ways can contemporary modes of reading the past serve to freshly illuminate not only the contours of that same past but also the very critical assumptions of the present upon which fields like medieval and early modern Hispanic Studies are built? In this way, Pornographic Sensibilities encourages at once both rigorous historicizations of pre- and early-modern culture, and playful engagement with "presentism," considered here as a critical tool to undress the hidden assumptions of both past and present. This move substantively challenges long-held critical orthodoxies among scholars of pre-Enlightenment periods, for whom the very category of "pornography" itself has often problematically been framed as an anachronism when applied to their work.